Plan de marketing para la empresa de electrodomésticos “Créditos A & O”, de ventanas. - Orellana Villegas, Daysi Marlen (2012)
The research began motivated by the author desire of improving the market share of a small business, Créditos A&O, that trade appliances in Ventanas, where this market is highly competitive, and it is dominated by big and already recognized national brands. As a first step, it was defined the direction of the research, identifying the main problem, which was the lack of a marketing plan in Créditos “A&O” that doesn´t allow the company to effectively compete with its competitors in Ventanas, affecting the performance of its sales. Once the problem was identified, the main objective of the research was established: elaborate a marketing plan for Créditos A & O. To reach the main objective the research was divided into two parts: the documental and the field research. To start with the first one, it was necessarily to study specialized information of recognized authors (Kotler, Cortina, Muñiz, Trespalacios, Armstrong and others), in subjects as: market research, research plan, research tools, samples, sales, and marketing plan. These studies allow the author to improve the knowledge about the problem, and correctly direct the research. The field research was done by using surveys, which were applied to a sample of clientes and potential clientes of the company. The survey results gave important information like, the company is not in the top of mind of the appliances consumers in Ventanas, the 58% of the actual clients do not remember when and what was the last promotion of Créditos A&O, the clients agree in a 95% that the company needs to improve its marketing campaign, and other information that let the author know the aspects that need to be improved. The research helped to define a potential solution for the identified problem, which is based in the development of a Promotion and Advertising Plan that allows the company to improve its market share and number of clients by using a new image and better promotions.